Left subclavian artery pseudoaneurysm after blunt chest trauma with left upper extremity ischemia - Muddasir Ashraf, MD, MS; Irina Goncharova, MD; M. Fuad Jan, MD; Lakshmi Muthukumar, MD; Tanvir Bajwa, MD; Mark Mewissen, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
We describe a 74-year-old male with delayed onset of acute left upper extremity ischemia after blunt chest trauma with left clavicular fracture, resulting in left subclavian artery injury, including pseudoaneurysm formation, intramural hematoma, thrombosis, and distal embolization to the brachial artery. The patient presented with left upper extremity pain, forearm and hand numbness, and digital cyanosis. The patient was treated with a hybrid approach, consisting of transfemoral percutaneous deployment of a covered stent in the left subclavian artery and concomitant surgical thrombectomy of the left brachial artery, resulting in excellent recovery and resolution of symptoms.